Influence of Thyroid Peroxidase Antibodies Serum Levels in Graves' Disease - Guia Lopes, Maria L (2023)
Purpose Graves' disease (GD) is an autoimmune disorder caused by the presence of antibodies to the thyroid stimulating hormone (TSH) receptor (TRAbs), usually presenting with clinical signs of hyperthyroidism. Previous evidence suggests that higher serum levels of thyroid peroxidase antibodies (TPOAbs) may lead to more sustained remission of hyperthyroidism after treatment with antithyroid drugs (AT). However, doubts about the influence of TPOAbs in Graves' disease outcomes still remain. Methods A retrospective, unicenter cohort study was performed. All patients with GD (TRAbs > 1.58U/L), biochemical primary hyperthyroidism (TSH < 0.4 µUI/mL), and TPOAbs measurement at diagnosis, treated with AT between January 2008 and January 2021, were included for analysis. Results One hundred and forty-two patients (113 women) with a mean age of 52 ± 15 years old were included. They were followed up for 65.4 ± 43.8 months. TPOAbs positivity was present in 71.10% (n=101) of those patients. Patients were treated with AT for a median of 18 (IQR (12; 24)) months. Remission occurred in 47.2% of patients. Patients with remission presented with lower TRAbs and free thyroxine (FT4) levels at the diagnosis. (p-value <0.001, p-value 0.003, respectively). No association was found in the median TPOAbs serum levels of patients who remitted and those who maintained biochemical hyperthyroidism after the first course of AT. Relapse of hyperthyroidism occurred in 54 patients (57.4%). No difference was found in TPOAbs serum levels regarding the patient's relapse. Moreover, a time-based analysis revealed no differences in the relapse rate after 18 months of AT therapy between patients with and without TPOAbs positivity at the diagnosis (p-value 0.176). It was found a weak positive correlation (r=0.295; p-value <0.05) between TRAbs and TPOAbs titters at the moment of Graves' diagnosis. Conclusion In this study, a correlation between TRAbs measurements and TPOAbs titter was described, although no significant association was found between the presence of TPOAbs and the outcomes of patients with GD treated with AT. These results do not support the use of TPOAbs as a useful biomarker to predict remission or relapse of hyperthyroidism in GD patients.